Low-grade endometrial stromal sarcoma metastatic to the breast: Immunohistochemical and molecular characterization of an unusual mimic of mammary myofibroblastoma - Daffolyn Rachael Fels Elliott; Melike Pekmezci; Katherine B. Geiersbach; Gregor Krings; Joseph T. Rabban; Charles Zaloudek; Yunn-Yi Chen (Elsevier, 2020)
We present a case of low-grade endometrial stromal sarcoma (ESS) that metastasized to the breast 25 years after the original diagnosis, with clinical, radiographic and pathologic follow-up data. The diagnosis of metastatic ESS was supported by the morphologic features of the breast tumor and its immunohistochemical profile, which included positive staining for CD10, WT1, estrogen receptor (ER) and progesterone receptor (PR). The diagnosis of metastatic ESS was confirmed by fluorescence in situ hybridization (FISH) testing, which revealed a characteristic JAZF1 gene rearrangement. The unusual clinical presentation raised a differential diagnosis that included mammary myofibroblastoma of the breast. We compared the morphologic characteristics and immunohistochemical profile of 15 low-grade ESS cases (8 primary and 7 metastatic) to eight cases of mammary myofibroblastoma. Immunostains that differentiated between these entities included CD34, retinoblastoma protein (Rb) and FOXL2. The pathologist can play a key role in the recognition of uncommon metastases to breast, and although rare, metastatic low-grade ESS should be included in the differential diagnosis of spindle cell tumors of the breast.